Group Communication Strategies for Resolving Conflicts in KKN (Community Service Program) Activities - Wildan Nurbayan; Sri Wulandari; Dian Andriany (CV. Syntax Corporation Indonesia, 2026)
KKN (Community Service Program) places students in temporary work groups with diverse backgrounds and personalities, making potential conflicts inevitable. This study aims to identify the process of group communication, identify conflicts that arise in group communication, and analyze group communication strategies in resolving conflicts in KKN activities in Ciledug District, Cirebon Regency, specifically Group 62 Jatiseeng Village and Group 63 Ciledug Kulon Village. This study uses a qualitative descriptive method with data collection techniques through in-depth interviews, participatory observation, and documentation. The results of the study show that the strategies used to manage conflict in KKN activities include deliberation, discussion, and interpersonal communication. The implementation of effective strategies that prioritize openness, empathy, and participation in resolving conflicts can ensure smooth cooperation and the sustainability of KKN activities. This study confirms that conflicts need not be avoided, but can be resolved effectively using appropriate group communication strategies.